The Influence of the Relationship between Foundation Management and School Principals on School Performance: Case Study at XYZ School - Abdul Wahid Mahsuni; Achmad Agus Priyono (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
This research examines the relationship between foundation administrators (principals) and school principals (agents) on school performance, with a focus on teacher performance. Using a quantitative approach, this research analyzes the quality of communication, level of trust, and support between principals and agents in influencing school performance. Research findings show that both foundation management and principal leadership have a significant impact on individual teacher performance, and when combined, the impact is greater. The practical implications of this research suggest establishing discussion forums, identifying training needs, conflict mediation approaches, promoting synergy and collaboration, as well as fostering good relationships between foundation administrators and teachers as strategies to improve teacher performance and the overall quality of education